Modernization and the Role of the Military as a Vehicle of Modernization - Arafat, Md. Yeasir; Fahmida, Fahmida (HISTORICAL: Journal of History and Social Sciences, 2026)
Modernization is the process through which societies transform from traditional structures to modern systems, involving economic, political, social, and cultural change. The military, as one of the most organized and disciplined institutions, often serves as a vehicle for modernization by introducing technological innovations, fostering national unity, developing infrastructure, and promoting education and skills. However, military-led modernization faces challenges, including lack of democratic legitimacy, overcentralization of power, inequality, cultural conflicts, and sustainability issues. This research explores the concept and nature of modernization, examines the role of the military in facilitating societal change, and provides a balanced perspective on the limitations and potential of military-driven modernization. The study highlights that while the military can accelerate modernization, sustainable and inclusive development requires cooperation with civilian institutions and democratic governance.